Pengaruh Dosis Pupuk Organik Cair Terhadap Pertumbuhan Tanaman Sawi (Brassica Rapa L.) Dengan Sistem Vertikultur Di Kelurahan Tambaksari Surabaya - Chrystia Aji Putra; Wahyu Riska Ardila; Rico Widi Taruna Nugroho; Muhammad Naufal Devano; Nurmala Erlyawati; Muchammad Fatchur Rachman Wahyudi (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2023)
Vegetable plants are commodities that are always consumed by people fresh and can be a source of vitamins, minerals and contain antioxidants that can inhibit the growth of cancer cells. Mustard greens are one of the vegetable commodities that are considered the best. The unique thing about mustard greens is that they can grow well in low and highlands. This research was carried out for 10 days, this research started on 27 November 2023 to 09 December 2023. The location of this research was at Balai RW 01, Tambaksari Village, Surabaya City, East Java. Data collection starts from the first day after planting the mustard seeds. Subsequent data collection was carried out every 3 days until the 10th day. The research results showed that the best POC dose for the growth of pak choy mustard greens was 40 ml/l water (P2). By administering a dose of 40 ml/l of water to mustard plants, they can produce a height of up to 16 cm and a number of leaves of 14 at 10 HSPT.